Sosialisasi "Tolak Politik Uang" Komisi Pemilihan Umum Kota Jakarta Selatan Sebagai Upaya Melek Politik Di Kalangan Pemilih Muda dalam Pilkada Jakarta 2024 - Putri Lestari; Andys Tiara; Yulia Rahmawati (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to understand the socialization carried out by the South Jakarta City KPU in an effort to promote political literacy among young voters in the 2024 DKI Jakarta gubernatorial election. This research focuses on the efforts of the South Jakarta City KPU to socialize young voters about the importance of rejecting money politics, as well as examining the effectiveness of the socialization programs conducted. The methodology used is a descriptive method with a qualitative focus. The results of the study show how this socialization contributes to the increase in political awareness among young voters. This includes measuring their knowledge about voter rights, the electoral process, and the consequences of engaging in money politics. Analysis of the methods and media used in socialization is also an important focus. The research can cover the types of media (such as through film media and socialization) used by the KPU of South Jakarta, as well as how these communication strategies are tailored to attract the attention of young voters. In this case, this research aims to provide a comprehensive overview of how the South Jakarta City KPU conducts the "Reject Money Politics" campaign as an effort to increase political awareness among young voters, as well as the challenges and successes faced in the process.